2020
DOI: 10.33963/kp.15518
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical circulatory support restores eligibility for heart transplant in patients with significant pulmonary hypertension

Abstract: HF and is considered one of key contraindications to orthotopic heart transplant (OHT). 2,9 Reversing increased pulmonary capillary pressure represents a therapeutic challenge, which would make OHT-a final resolution of congestive HF-possible. There have been few studies that analyzed the impact of CF-LVAD implantation on pulmonary pressure and resistance. Some authors INTRODUCTION A constant increase in the number of patients with end-stage heart failure (HF) and a shortage of heart donors worldwide implies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…LVAD therapy also decreases the pulmonary artery pressures and pulmonary capillary wedge pressure (PCWP) (6,7). This is also the case in many patients with fixed pulmonary hypertension, giving them the opportunity to be transplanted after LVAD therapy (8).…”
Section: Hemodynamics Of Lvad Patientsmentioning
confidence: 99%
“…LVAD therapy also decreases the pulmonary artery pressures and pulmonary capillary wedge pressure (PCWP) (6,7). This is also the case in many patients with fixed pulmonary hypertension, giving them the opportunity to be transplanted after LVAD therapy (8).…”
Section: Hemodynamics Of Lvad Patientsmentioning
confidence: 99%
“…6 It has even been demonstrated that LVAD can reduce PVR in patients with established PH and thereby make them suitable for transplantation. [7][8][9] The fact that LVAD support may reduce RV afterload (i.e. PVR) at time of transplantation might be beneficial for post-operative allograft RV function.…”
Section: Introductionmentioning
confidence: 99%
“…Besides increasing CO, this treatment results in reduced pulmonary arterial wedge pressure (PAWP) and PVR 6 . It has even been demonstrated that LVAD can reduce PVR in patients with established PH and thereby make them suitable for transplantation 7–9 . The fact that LVAD support may reduce RV afterload (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The success of continuous-flow left ventricular assist device (cf-LVAD) therapy is reduced by several severe complications like hemorrhagic and thromboembolic events, arrhythmias, multi-organ failure, and driveline infections [ 1 4 ]. Driveline infections are the most common adverse event, occurring in about 28% of all patients with an implanted cf-LVAD [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%